Численность птиц в лесах различных типов Ворошиловградской области - Панченко, С.Г. (Вестник зоологии, 1975)
On the basis of data of birds seven-year registration a quantitative characteristics of the spring-summer ornitofauna is given for different constructions of tree plantations in the Voroshilovgrad region. 14 species of 54 registered dominate in all ypes of forests. They account for 68% of the total number of the registered birds. In droughty years the number of birds in forests of all the studied types is twice-thrice as low.